A new species of Chonala Moore, 1893 (Lepidoptera: Nymphalidae) from northeastern India - Kunte, Krushnamegh; Khan, Fahim; Pawar, Ujwala (Zootaxa, 2026)
We describe a new species of nymphalid butterfly, Chonala albistricta sp. nov. (Satyrinae: Satyrini) from Mayodia pass, Lower Dibang Valley District, Arunachal Pradesh, India, based on two male and one female specimens. The new species may be distinguished from the similar C. masoni (Elwes, 1882) by a distinctly narrower, unevenly bent white band on the forewing and other morphological traits, and differences in the tip of valve of the male genitalia. Additional notes are provided on the distributional range, habits and habitat, and phenology.